Quantitative evaluation of mixed biomass burning and anthropogenic aerosols over the Indochina Peninsula using MERRA-2 reanalysis products validated by sky radiometer and MAX-DOAS observations - Takeru Ohno; Hitoshi Irie; Masahiro Momoi; Arlindo M. da Silva (Progress in Earth and Planetary Science, 2022)
Abstract In this study, we conducted the quantitative evaluation of aerosol optical properties in the Indochina Peninsula (ICP), which is significantly affected yearly by both biomass burning (BB) and anthropogenic aerosols, using Modern-Era Retrospective Analysis for Research and Applications, version 2 (MERRA-2) aerosol products. To perform spatiotemporal analysis with validated aerosol data, the MERRA-2 aerosol optical depth (AOD) and absorption AOD (AAOD) data were evaluated based on sky radiometer observations at the SKYNET Phimai site (15.18° N, 102.56° E). Furthermore, multi-axis differential optical absorption spectroscopy was conducted, providing additional data for the comparison of the aerosol extinction coefficient (AEC) vertical profile data. MERRA-2 AOD, AAOD, and AEC at altitudes below 1 km were underestimated in the dry season, with relative mean biases of 0.84, 0.54, and 0.48, respectively. These underestimations are attributed to insufficient BB emissions of light-absorbing aerosols near the surface. On the basis of these results, we investigated the factors that determined spatiotemporal variations in AOD over ICP from 2009 to 2020. We found that the seasonal variations in AOD were driven mainly by organic carbon (OC) and sulfate aerosols. OC AOD was dominant during the active BB period (from January to March), whereas sulfate AOD was high all year round, accounting for more than 25% of the total AOD. Sulfate AOD in the northeast ICP (NEIC) was approximately 74% of the total AOD in October, indicating the remarkable effect of sulfate aerosol transportation from southern China (SC). In the period of study, AOD decreased in NEIC and south ICP (SIC) by − 4.40% and − 3.00% year−1, respectively, corresponding to the decrease in sulfur dioxide concentrations in SC and NEIC. Thus, OC AOD was dominant during the active BB periods, whereas a significant amount of anthropogenic aerosols from SC contributed to the atmospheric environment over ICP throughout 2009–2020.